AuPd nanoparticle-decorated ultrathin Bi2TiO4F2 sheets for photocatalytic methane oxidation. (24th May 2022) - Zhao, Yibo; Luo, Jieyue; Hu, Huijie; Shen, Jinni; Zhang, Zizhong; Yuan, Rusheng; Huang, Haowei; Long, Jinlin
Abstract : Ultrathin Bi2 TiO4 F2 with highly dispersed AuPd alloy nanoparticles as cocatalysts enables efficient photocatalytic conversion of methane to methanol with 93.5% selectivity at ambient temperature. Abstract : Bi2 TiO4 F2 nanosheets with abundant polarity surfaces make them a good candidate photocatalyst for CH4 activation. Decorated with AuPd alloy nanoparticles, highly efficient CH4 to CH3 OH transformation of 277.32 μmol g −1 h −1 with 93.5% selectivity is achieved over a AuPd/Bi2 TiO4 F2 nanosheet photocatalyst, which is 7.4 times higher than that of the pristine Bi2 TiO4 F2 nanosheets.